2022
DOI: 10.3389/fchem.2022.895483
|View full text |Cite
|
Sign up to set email alerts
|

Novel Coumarin–Pyridine Hybrids as Potent Multi-Target Directed Ligands Aiming at Symptoms of Alzheimer’s Disease

Abstract: In this research, a series of coumarin-based scaffolds linked to pyridine derivatives via a flexible aliphatic linkage were synthesized and assessed as multifunctional anti-AD agents. All the compounds showed acceptable acetylcholinesterase (AChE) inhibition activity in the nanomolar range (IC50 = 2–144 nM) and remarkable butyrylcholinesterase (BuChE) inhibition property (IC50 = 9–123 nM) compared to donepezil as the standard drug (IC50 = 14 and 275 nM, respectively). Compound 3f as the best AChE inhibitor (IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Self-mediated Aβ1–42 aggregation inhibition was assessed via thioflavin T (ThT) fluorescence assay ( Rosini et al, 2008 ; Wang et al, 2018 ; Babaei et al, 2022 ). As shown in Table 1 , both CQ and MT showed good anti-aggregation effect.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-mediated Aβ1–42 aggregation inhibition was assessed via thioflavin T (ThT) fluorescence assay ( Rosini et al, 2008 ; Wang et al, 2018 ; Babaei et al, 2022 ). As shown in Table 1 , both CQ and MT showed good anti-aggregation effect.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, more and more researchers have turned their attention to the multi-target design strategy. Multi-target drugs are expected to become a breakthrough in the treatment of AD ( Rossi et al, 2021 ; Babaei et al, 2022 ; Turgutalp et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, no significant cytotoxic effects were observed for 177 in SH-SY5Y and HepG2 cell lines and a neuroprotective effect against both Aβ 1−42 and H 2 O 2 induced neuronal damage was exerted ( Rullo et al, 2022 ). Khoobi et al exploited the capability of pyridinium salt to interact with the catalytic anionic site of AChE developing a new class of coumarin derivatives cross-linked with pyridinium salt ( Babaei et al, 2022 ). The most active compound 178 was able to inhibit both AChE and BuChE with IC 50 values of 2.0 nM and 24.0 nM ( Figure 1A ), respectively, showing higher potency than donepezil (IC 50 = 14.0 nM on AChE, IC 50 = 2750 nM on BuChE; Structure not shown) used as reference.…”
Section: Biological Applications Of Coumarin Derivativesmentioning
confidence: 99%
“…E. Babaei et al reported coumarin pyridine hybrids via a flexible aliphatic linkage were synthesized and assessed their anti-Alzheimer activities [42]. All coumarin pyridine hybrids found potential acetylcholinesterase (AChE) inhibition activity in the nanomolar range (IC50 = 2-144 nM) and remarkable butyrylcholinesterase (BuChE) inhibition property (IC50 = 9-123 nM) compared to donepezil as the standard drug (IC50 = 14 and 275 nM, respectively).…”
Section: Review Literature Of Anti-alzheimer Potential Of Coumarin De...mentioning
confidence: 99%